PENERAPAN PRAKTIKUM JARAK JAUH PADA TOPIK PERTUMBUHAN MIKROBA DALAM MASA DARURAT COVID-19 DI INSTITUT TEKNOLOGI SUMATERA - Fina Khaerunnisa Frima (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2020)
As emerged the Coronavirus Disease (COVID-19) outbreak in Indonesia, causing the increased number of death. Ministry of Education and Culture of Indonesia allowed the distance learning method due the prevention of transmission COVID-19. Institut Teknologi Sumatera ordered the implementation of distance learning method by accessing the online courses since 18th March 2020 to 29th May 2020. One of the obstacle for implementation the distance learning in Departement of Chemistry is the achievement of practical skill competencies. This study describes the implementation of alternative laboratory practice in home at one of biochemistry topic using daily chemical and been adjusted with Department of Chemistry learning outcomes and curriculum. Design of this study is one-shot case study and subjects were the 92 of second year college students at Department of Chemistry, Institut Teknologi Sumatera. Instruments of this study are quesioner guideline and student practicum report. The result of implementation the alternative laboratory practice in home were 71.7% of students well-understood the instruction in handbook, 82.6% of students agreed that the topic of distance laboratory practice been accordance with the curriculum, and 80.4% of students were able to elaborate other useful topic of implementation laboratory practice in daily life. Around 86.9% of students could make the good practicum report. Implementation of chemistry laboratory practice using daily chemical in home could be considered as one of alternative distance laboratory practice to achieve the practical skill competencies.